The Location of Medieval Kotobrzeg and the Finds of Pottery as Evidence of Social Changes - Rebkowski, Marian (Hikuin, 1998)
During the past decade Polish archaeologists have become much more interested in the towns of the late Middle Ages. Particularly interesting results have arisen from excavations in the coastal towns of Medieval Hanseatic origin. Kotobrzeg is one of these towns; it lies on the coast, on the right bank of the estuary of the River Parsta.